PENGARUH LIKUIDITAS DAN STRUKTUR MODAL TERHADAP PROFITABILITAS PADA PERUSAHAAN PLASTIK DAN KEMASAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Dedek Kurniawan Gultom (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
The objective of the research was to analyze the influence of Liquidity and Capital Structure on Profitability Plastics and Packaging Company in the period of 2006-2011 in IDX either partial or simultant. Analysis technique used is multiple linear regression analysis, t test, F test and the coefficient of determination. Processing of the data in this study using the program SPSS 16.0 for Windows software. Based on the results of this study concluded that the Liquidity and Capital Structure variables simultaneously have a significant impact on profitability. While partially is liquidity has a significant influence on the profitability and capital structure has no significant effect on the profitability.